A Study of Causes of Unwanted Pregnancies in Mothers who Reffered to Hospitals of Hamadan - Gita Sangestani (پزشکی بالینی ابن سینا, 1995)
A prospective cross sectional study was conducted with goal of  Identifying of causes & unwanted pregnancies in mothers who referred to Hamadan hospitals. 384 mothers as Convenience sampling were included. Results indicate that from 384 pregnant mothers, 42% had unwanted pregnancies. The causes were: (a) incorrect use of contraceptives (b) the failure rate of contraceptives (c) non use of Contraceptives.